Student perceptions of patient safety incident reporting while on placement - Gavin Johnson; Jessica Runacres; Edward Tolhurst (Journal of Paramedic Practice, 2026)
Background: Reporting of patient safety incidents is persistently lower than would be expected in the NHS ambulance service. Aims: This study explored student paramedics' perceptions of safety incident reporting during practice placements, including barriers and facilitators to this. Methods: An online qualitative questionnaire was distributed to undergraduate paramedics who had completed at least one period of practice placement at levels 4–6. Responses were analysed using reflexive thematic analysis. Findings: Forty-five students completed questionnaires. Three themes arose: professionalism and moral duty of care; relationships and support; and fear of repercussion and judgement. Students described a strong ethical intent to report, particularly where severe harm occurred, but felt uncertain about processes for low-harm events, whether they could rely on mentors and psychologically safe teams. Conclusion: Reporting intentions were shaped by interactions between professional values, placement relationships and perceived psychological safety. Clearer reporting guidance for students and more consistent placement support may strengthen learning-focused reporting cultures.